KAPASISTAS SALURAN SUNGAI KAROMBASAN - Anggraini F. M. Pandeirot; Johan A. Rombang; Fabiola B. Saroinsong (COCOS, 2018)
ABSTRACT Capacity Of Karombasan River Channels  The Karombasan watershed has an area of 270 ha and river length of 3.058 m. The main river, Karombasan River, floods almost every year, possibly because the river channel is not able to accommodate the volume of the flow and thus causing a number of houses on the riverbank to be flooded. This flooding event is very disturbing to the locals. The purpose of this research is to analyze the river in location that often flood. Sampling and observation points were determined through purposive sampling methods at the points of frequent flooding. River capacity was analyzed using the Manning equation. Analysis of current river capacity from points 1 to 5 is 10,82 m³/s, 7,85 m³/s, 12,19 m³/s, 11,03 m³/s, and 5,32 m³/s, respectively.  Keywords : Watershed, flood, river capacity.